Vibration signatures in ball bearings as a function of lubricant viscosity ratio κ, under alternating lubrication conditions. (April 2021) - Jakobsen, Morten Opprud; Herskind, Eskild Sune; Bjerge, Kim; Ahrendt, Peter; Pedersen, Christian Fischer; Knudsen, Mikael Bergholz
Abstract: This paper analyses the vibrations emitted by a set of grease lubricated ball bearings run under load, when lubrication conditions alternate between good and insufficient. Conditions are varied by adjusting the operational parameters rotational speed and temperature. The dependency of the vibration signature on the lubrication ratio κ is considered. The results show a good correlation between κ and spectral kurtosis for a given frequency band, a : when the bearing is new, and b : when κ is below 0.6. Highlights: Insufficient lubrication through variation of speed and temperature. Varying operational conditions. Vibration analysis on transcient signals.